Evidence that aggregation of mouse sperm receptors by ZP3 triggers the acrosome reaction (The Rockefeller University Press, 1989)
In the mouse, considerable evidence indicates that initial sperm binding to the zona pellucida (ZP) is mediated by ZP3. In addition, this same glycoprotein is also responsible for inducing the acrosome reaction (AR). Whereas the O-linked oligosaccharides of ZP3 appear to mediate sperm-ZP binding, the portion of ZP3 bearing AR activity has not been defined. To try to understand the bifunctional role of ZP3 (binding and AR inducing activities), we have examined the hypothesis that ZP3 aggregates sperm receptor molecules. By analogy with findings in a variety of other extracellular signal transducing systems, including receptors for growth factors and insulin, this aggregation event could initiate the cascade resulting in the AR. To test this hypothesis, we have generated monospecific polyclonal antibodies against ZP2 and against ZP3, and examined the effects of these probes on capacitated sperm incubated in the absence or presence of various ZP protein preparations. For some experiments, we have used proteolytic fragments of ZP3, a preparation known to retain specific binding, but not AR-inducing, activity. We show here that capacitated mouse sperm, incubated with ZP glycopeptides, displayed ARs when incubated subsequently with anti-ZP3 IgG; ARs did not occur when parallel sperm samples were incubated with anti-ZP2 IgG or with anti-ZP3 Fab fragments. When capacitated sperm were treated successively, with (a) ZP3 glycopeptides, (b) anti-ZP3 Fab fragments, and (c) goat anti-rabbit IgG, ARs occurred in the majority of sperm. An alternative approach to examine this hypothesis used ZP proteins obtained from tubal eggs treated previously with bioactive phorbol diester (12-O-tetradecanoyl phorbol-13-acetate [TPA]). This preparation arrests capacitated sperm in an intermediate state of the AR. We demonstrate here that these sperm can be induced to undergo a complete AR by subsequent treatment with anti-ZP3 IgG. Together, these findings are consistent with the hypothesis under examination, and suggest that the aggregation of sperm molecules recognized by ZP3 glycopeptides or by TPA-treated ZP is sufficient to trigger the events that occur during acrosomal exocytosis.